Penggunaan Rating of Perceived Exertion dalam Berbagai Komponen Biomotor Latihan - Gafur Ammar Santoso; Berliana Berliana; Boyke Mulyana (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2021)
Coaches and athletes must be able to know whether the exercise carried out can affect optimal performance, coaches must have the ability to know the relationship between training load and training response (lambert borresen 2010) using Rating of Perceived Exertion (RPE). This study aims to determine the effectiveness of RPE to measure athletes' efforts in the biomotor components of speed, strength and endurance training. The research method used in this study was an experimental method, with the design of The One-Shot Case Stud), 11 swimming athletes and 6 diving athletes, the study was conducted in 3 sessions. To assess RPE during a training session (SPRE), standard instructions and statutory procedures are explained during a socialization session, samples are asked to assess the exertion of energy felt after the completion of a particular exercise execution based on the RPE CR-10 scale.